Metformin upregulates mitophagy in patients with T2DM: A randomized placebo‐controlled study - Shipra Bhansali; Anil Bhansali; Pinaki Dutta; Rama Walia; Veena Dhawan (2020)
Abstract Impaired mitochondrial autophagy (mitophagy) and NLRP3 inflammasome activation have been incriminated in the pathogenesis of T2DM. Metformin besides being an insulin sensitizer also induces autophagy; however, its effect on mitophagy and NLRP3 activation in patients with T2DM still remains elusive. Forty‐five drug‐naïve T2DM patients with HbA 1C 7%‐9% (53‐75 mmol/mol) were randomly assigned to receive either metformin, voglibose, or placebo for 3 months, and were also recommended for lifestyle intervention programme (n = 15 each). Mitochondrial oxidative stress (MOS) parameters, qPCR and immunoblotting of mitophagy‐related markers (PINK1, PARKIN, MFN2, NIX, LC3‐II, LAMP2), p‐AMPKα (T172), and NLRP3 proteins, as well as transmission electron microscopy (TEM) for assessing mitochondrial morphology were performed in the mononuclear cells of study patients. Both metformin and voglibose showed a similar efficacy towards the reduction in HbA 1c and MOS indices. However, multivariate ANCOVA divulged that mRNA and protein expression of mitophagy markers, NLRP3 and p‐AMPKα (T172), were significantly increased only with metformin therapy. Moreover, PINK1 expression displayed a significant positive association with HOMA‐β indices, and TEM studies further confirmed reduced distortions in mitochondrial morphology in the metformin group only. Our observations underscore that metformin upregulates mitophagy and subsequently ameliorates the altered mitochondrial morphology and function, independent of its glucose‐lowering effect. Further, restoration of normal mitochondrial phenotype may improve cellular function, including β‐cells, which may prevent further worsening of hyperglycaemia in patients with T2DM.